Adsorption of hydrogen sulfide from simulated waste water using locally –sourced adsorbents - Habeeb, Omar Abed (2018)
problems. The removal of H2S (aq) from a simulated petroleum refinery waste water using activated carbons produced from agricultural by-product such as, coconut shell (CNS), palm kernel shell (PKS), and wood sawdust (WSD) were investigated. The activated carbons obtained from the CNS, PKS, and WSD were chemically activated using KOH. The activated carbons (ACs) were modified by impregnating with calcium (Ca) extracted from egg shells to produce impregnated activated carbons (IACs) namely Ca-ACCNS, Ca-ACPKS and Ca-ACWSD. The prepared ACs and IACs were characterized using SEM/EDX, FTIR, BET, TGA, XRD and XPS. Comparative studies between all the six adsorbents for the removal of H2S (aq) from the simulated waste water were carried out. The adsorption studies revealed that Ca-modified PKS-based activated carbon (Ca-ACPKS) has shown best performance for the removal of H2S (aq). An optimization studies for the preparation conditions of the selected adsorbent (Ca-ACPKS) was investigated using Response Surface Methodology (RSM) and the optimum preparation conditions were found to be calcination temperature of 880 °C, calcium solution concentration of 49.31 %v, and calcination time of 57.5 min with removal efficiency of 99.2% and yield of 33.8%. Moreover, operating factors such as initial concentration of H2S (aq), adsorption contact time, dosage, pH of solution, and agitation speed were initially screened using 2 level factorial approach and the resulted significant factors were initial concentration of H2S (aq), adsorption contact time, and dosage were significant on the removal of H2S (aq). Furthermore, the effect of these three operating parameters were investigated using the central composite design (CCD) techniques of RSM and the optimum conditions obtained were initial concentration of H2S of 440 mg/L, adsorption contact time of 585 min, and dosage of 1.05 g Ca-ACPKS. The optimum operating conditions resulted in a removal efficiency of 99.5% with equilibrium concentration (0.5-2.2 mg/L) which was close to Department of Environment (DOE) standard B (0.5 mg/L) using real waste water. The kinetic studies of the adsorption behaviour of Ca-ACPKS have shown that Freundlich adsorption isotherm was fitted well and the adsorption process followed Pseudo- second order kinetic model. The maximum adsorption capacity of Ca-ACPKS was 543.4 mg/g. It can be concluded that Ca-ACPKS has an effective adsorbent for the removal of H2S (aq) from simulated waste water.